A novel N/Au co-doped carbon dot probe for continuous detection of silicate and phosphate by resonance Rayleigh scattering. Issue 17 (30th July 2019) - Li, Jiao; Li, Chongning; Zhang, Zhihao; Wang, Xiyin; Liang, Aihui; Wen, Guiqing; Jiang, Zhiliang
Abstract : Co-doped carbon dots are new multifunctional carbon nanomaterials. Abstract : Co-doped carbon dots are new multifunctional carbon nanomaterials. Their fast preparation and new analytical applications such as in continuous detection and resonance Rayleigh scattering (RRS) probes are of interest to people. Herein, the N/Au co-doped carbon dots (CDN/Au ) were prepared quickly by a microwave synthesis method using fructose as the carbon source and urea and HAuCl4 as dopants, and it exhibited an excellent RRS effect at 555 nm. Based on both silicate (SiO3 2− ) and phosphate (PO4 3− ) reacting with ammonium molybdate to form silicomolybdate heteropoly acid (SiMo) and phosphomolybdate heteropoly acid (PMo), PMo decomposed by the addition of citric acid, and SiMo/PMo combined with CDN/Au to show good RRS analytical properties, and a new strategy was developed to detect SiO3 2− and PO4 3− by the CDN/Au probes continuously. With the increase of SiO3 2− (PO4 3− ), SiMo (PMo) reacted with CDN/Au probes to form more big particles which resulted in the RRS intensity enhancement at 555 nm, and had a good linear relationship with the SiO3 2− (PO4 3− ) concentration in the range of 1.11 μg L −1 –19.98 μg L −1, with detection limits of 0.3 μg L −1 SiO3 2− and 0.3 μg L −1 PO4 3− . Accordingly, a new RRS method was established for continuous detection of SiO3 2− and PO4 3− using CDN/Au as the probe.